1980
DOI: 10.1128/jcm.12.1.105-111.1980
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus-Like, Calicivirus-Like, and 23-nm Virus-Like Particles Associated with Diarrhea in Young Pigs

Abstract: Virus particles morphologically similar to caliciviruses and rotaviruses were detected by electron microscopy (EM) in the intestinal contents of a 27-day-old diarrheic nursing pig. A third small spherical 23-nm virus-like particle was also observed. Calicivirus-like particles averaged 33 nm in diameter. Similar to rotaviruses, rotavirus-like particles were present as single-capsid 55-nm forms or double-capsid 70-nm particles. Most gnotobiotic pigs orally exposed to samples containing these three viruses develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
143
1
4

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(153 citation statements)
references
References 27 publications
(29 reference statements)
3
143
1
4
Order By: Relevance
“…Since a porcine SaV infection was first reported in the US in 1980s (Saif et al, 1980), it has only been reported in a few countries including the US, Netherlands, Venezuela and the United Kingdom (Bridger, 1990;Martínez et al, 2006;Saif et al, 1980). However, the precise epidemiology of porcine SaV infections in the other countries is not known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since a porcine SaV infection was first reported in the US in 1980s (Saif et al, 1980), it has only been reported in a few countries including the US, Netherlands, Venezuela and the United Kingdom (Bridger, 1990;Martínez et al, 2006;Saif et al, 1980). However, the precise epidemiology of porcine SaV infections in the other countries is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Porcine SaVs circulating in the US have been genetically analyzed using the major strains classified as SaV/GIII (Guo et al, 1999;Wang et al, 2005a), though one strain represents a potential new genogroup of porcine SaVs (Wang et al, 2005a). Since the discovery of porcine SaVs in the 1980s (Saif et al, 1980), only a few additional studies of their genetic diversity have been reported (Farkas et al, 2004;Guo et al, 1999;Schuffenecker et al, 2001;Wang et al, 2005a). In South Korea, we demonstrated that porcine SaVs cause diarrhea outbreaks .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Group C rotavirus (GCRV) was first detected in pigs in 1980 (Saif et al, 1980) and has been subsequently identified in humans, ferrets, and cattle (Rodger et al, 1982;Torres-Median, 1987;Tsunemitsu et al, 1991). Since then, the global distribution of human GCRVs has been established; they are suspected of being an emerging pathogen Caul et al, 1990;Esona et al, 2008;Iizuka et al, 2006;Kuzuya et al, , 2007Medici et al, 2009;Steyer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, NoVs and SaVs have been associated with enteric diseases only, and are the most common cause of food-and waterborne, acute, non-bacterial gastroenteritis in humans worldwide (Green et al, 2001). Animal SaVs and NoVs also cause gastroenteritis in swine, calves and mink (Bridger, 1990;Guo et al, 2001;Saif et al, 1980).…”
Section: Introductionmentioning
confidence: 99%